PERAN AMERIKA SERIKAT DALAM KERJASAMA PENANGGULANGAN PERDAGANGAN NARKOTIKA DI MEKSIKO 2007-2012 - Saraswita, Putu Intan; Dharmiasih, S.IP., MA, D.A. Wiwik; Resen, S.IP., MA, Putu Titah Kawitri (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2014), 2014)
ABSTRACT Drug trafficking is a form of cross-border crime and a serious threat to global security. Drug trafficking activities carried out by the Mexican drug trafficking organization has led to a variety of security instability in Mexico and cause spillover into the United States. The efforts made the United States and Mexico to combat drug trafficking through the Merida Initiative refers to the United Nations against Illicit Traffic in Narcotic Drug and Psychotropic Substances 1988 Bilateral cooperation United States and Mexico also involve the United States law enforcement agencies such as the FBI and DEA. Therefore, this research aimed to describe the role of the United States by the FBI and DEA in the fight against drug trafficking in Mexico. This research uses the concepts of Transnational Organized Crime and International Cooperation Theory. Keyword: Transnational Organized Crime, International Cooperation, FBI, DEA